Groundwater quality on a waste disposal area due to sand mining activities in São Paulo state, Brazil - Bonotto, Daniel Marcos [UNESP]; de Oliveira, E. G. [UNESP] (WITPRESS LTD., 2011)
This investigation reports the results of a study realized in an area related to the development of sand mining activities, which belongs to Sibelco Mineração Ltd. The site is located around Analândia municipality, nearly in the center of São Paulo State, Brazil. Hydrochemical analyses of groundwater were realized under different periods of time, with the aim of evaluating the possibility of release of several constituents to the liquid phase, which may be a source of pollution of the surface hydrological resources and of the deeper Guarani aquifer. This is because the site is located at the recharge area of Guarani aquifer and some tributaries from Corumbataí river may also be suffering contamination, implying on the impoverishment of the water quality that are very important resources in the region, as they are extensively used for drinking purposes, among others.© 2011 WIT Press.
Keywords: Elemental concentrations; Groundwater; São Paulo state; Sand mining activities; Trace and heavy metals; Water quality; Ground-water qualities; Guarani aquifer; Hydrochemical analysis; Hydrological resources; Liquid Phase; Recharge area; Sand mining; Aquifers; Environmental engineering; Groundwater resources; Heavy metals; River pollution; Waste disposal; Groundwater pollution